2019
DOI: 10.1038/s41467-019-10571-9
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved molecular dynamics of single and double hydrogen migration in ethanol

Abstract: Being the lightest, most mobile atom that exists, hydrogen plays an important role in the chemistry of hydrocarbons, proteins and peptides and most biomolecules. Hydrogen can undergo transfer, exchange and migration processes, having considerable impact on the chemical behavior of these molecules. Although much has been learned about reaction dynamics involving one hydrogen atom, less is known about those processes where two or more hydrogen atoms participate. Here we show that single and double hydrogen migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
59
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 49 publications
(49 reference statements)
7
59
1
Order By: Relevance
“…Our results show increases in D 2 H + and D + 3 yields, as well as an increasing D 2 H + :D + 3 ratio, for positive linear chirp, with a maximum around φ (2) +250 fs 2 . This is in direct contrast to the result of Shirmel and co-workers who reported that negative linear chirp increases the yield of H + 3 and other fragments from ethane, with a maximum at φ (2) ≈ − 1000 fs 2 . They also report an essentially constant D 2 H + :D + 3 ratio as a function of chirp.…”
Section: Dissociation Channelcontrasting
confidence: 99%
See 2 more Smart Citations
“…Our results show increases in D 2 H + and D + 3 yields, as well as an increasing D 2 H + :D + 3 ratio, for positive linear chirp, with a maximum around φ (2) +250 fs 2 . This is in direct contrast to the result of Shirmel and co-workers who reported that negative linear chirp increases the yield of H + 3 and other fragments from ethane, with a maximum at φ (2) ≈ − 1000 fs 2 . They also report an essentially constant D 2 H + :D + 3 ratio as a function of chirp.…”
Section: Dissociation Channelcontrasting
confidence: 99%
“…As shown in Figure 4C, there are a number of combinations of pulse parameters that reach nearly the same level of effectiveness at manipulating the D 2 H + :D + 3 ratio as the optimized pulse. The highest values of the D 2 H + :D + 3 ratio are seen at negative values of both φ (2) and φ (3) . In this region of parameter space, the yield of the individual channels have both been reduced by roughly a factor of 10.…”
Section: Dissociation Channelmentioning
confidence: 91%
See 1 more Smart Citation
“…As a consequence of the displacement of hydrogen atoms, significant structural rearrangements could be triggered, leading to isomerization and thus alter the chemical functions of those molecules. In particular, for the ionic organic molecules, numerous studies have been conducted to elucidate the formation and evolution of ultrafast hydrogen migration through the sophisticated momentum imaging techniques [5][6][7][8][9][10][11][12][13][14][15][16][17] . It has been found that the hydrogen-migration channel can dominate over direct fragmentation in molecular cations 5 .…”
mentioning
confidence: 99%
“…It has been found that the hydrogen-migration channel can dominate over direct fragmentation in molecular cations 5 . In addition to the well-known single hydrogen migration, another more complicated process, that is, the double hydrogen migration has been proven to play a more important role than generally assumed in molecular fragmentation 6 . Furthermore, in some of those hydrogen-migration studies special attention has been paid to the reaction dynamics in the course of H 3 + formation [12][13][14][15][16][17] .…”
mentioning
confidence: 99%